Tax harmonization of tax accounting procedures and income of industrial companies - Al-Zameli, Ahmed Kadhim Sendw, Shaymaa Abdulhusein Abdulkadhim Alisawi Shaymaa, Ali Abdul-Hussein Hani (Opción, 2019)
This research aims to investigate the Tax harmonization of financial accounting procedures and the income of companies especially the industrial companies via comparative qualitative research methods. As a result, the different distribution of companies among the alternatives seems to be statistically significant (at the 0.05% level) in the case of deferred taxation, leasing. In conclusion, the implementation of a tax harmonization procedure creates coherence by which we can attain our tax objectives in a better way, at least for industrial companies.